Magma evolution during the post-rift phase of the Santos Basin, Brazil: petrogenesis and geochemistry of ∼126–121 ma basalts and diabases - He, Wenyuan; Wang, Hongping; Su, Jinglin; Wang, Wangquan; Zhao, Junfeng; Zuo, Guoping; Wang, Tongkui; Yang, Liu; Ren, Kangxu; Wang, Chaofeng; Zhao, Jian; Guo, Yuan; et al. (Frontiers in Earth Science, 2025)
The Santos Basin, a passive continental margin basin recognized for its vast deep-sea hydrocarbon potential, poses unique geological issues due to the large amount of igneous rocks revealed by drilling data. In order to understand the magmatic evolution during the post-rift phase, we studied petrology, major elements, trace elements, and Sr-Nd isotopic composition of bulk rock, and Ar-Ar dating on whole rock and minerals on basalts and diabases from Santos Basin. Ar-Ar dating results suggest that basalts and diabases emplaced on ∼126–121 Ma. The geochemistry and Sr-Nd isotopic compositions indicates the derivation of these rocks from the spinel and garnet lherzolite facies, denoted by increased La/Sm ratios that suggest a 1%–5% degree of partial melting. These findings correspond with the characteristics of continental rift basalts. The geochemical analysis hints that the older basalts and diabases were likely derived from the asthenospheric mantle, whereas the younger ones display a geochemical mix indicative of contributions from both the deeper asthenosphere and the subcontinental lithospheric mantle (SCLM), or possibly from crustal contamination. A proposed hypothetical model indicating that the deepening of the basin into the asthenosphere, in conjunction with the thinning and stretching of the lithosphere, could have been instrumental in the magmatic events recorded in the region.